A Study on the Different Types of Breast Carcinoma in a Tertiary Care Centre with Immunohistochemical and Molecular Correlation - Mahajan, Adavelly Anil; Ajmal, Imran Thariq; Annamalai, Avinash; Anand, Felix Raj (Journal of Neonatal Surgery, 2025)
Background: Breast carcinoma represents a heterogeneous group of malignancies with diverse histological and molecular characteristics that significantly impact clinical management. Current diagnostic approaches integrate histopathological evaluation with immunohistochemical (IHC) profiling and molecular analysis to enable precise classification and personalized treatment strategies. This study aimed to characterize breast carcinoma subtypes in a tertiary care setting through comprehensive pathological and molecular correlation. Methods: A prospective observational study was conducted on 30 histologically confirmed breast carcinoma cases. Clinicopathological parameters were recorded, and tumors were classified using WHO criteria. IHC analysis evaluated ER, PR, HER2/neu, and Ki-67 expression according to ASCO/CAP guidelines. HER2-equivocal cases underwent FISH confirmation. Molecular subtyping categorized tumors as Luminal A, Luminal B, HER2-enriched, or triple-negative. Statistical analysis included descriptive statistics and chi-square tests. Results: The cohort demonstrated characteristic age distribution (60% patients aged 40-60 years) with predominance of invasive ductal carcinoma (80%). IHC profiling revealed ER positivity in 60%, PR in 50%, and HER2 overexpression in 16.7% of cases. Molecular subtyping identified Luminal B (33.3%) as most frequent, followed by Luminal A (26.7%) and triple-negative (26.7%) subtypes. FISH analysis resolved 50% of HER2-equivocal cases as positive. Significant associations emerged between molecular subtypes and tumor grade (p<0.05), with aggressive subtypes showing higher-grade morphology. Conclusion: This study highlights the importance of integrated pathological and molecular characterization in breast carcinoma management. The observed predominance of Luminal B and triple-negative subtypes, along with their association with higher tumor grades, underscores the need for tailored therapeutic approaches. Findings emphasize the critical role of comprehensive biomarker testing, particularly in resolving diagnostically challenging cases, to optimize treatment strategies in diverse patient populations